Beware of Greeks bearing gifts: Cretan archaeology and the Dorian invasion - Judson, Catharine (Journal of Greek Archaeology, 2023)
In the 19th and early 20th centuries AD, when systematic excavations began to reveal evidence for major shifts in material culture and political structures after the destructions of the Mycenaean palaces, archaeology appeared to demonstrate the historical reality of a Dorian migration, previously known only from much later textual sources. In subsequent excavations, a distinct ‘Dorian’ assemblage failed to materialize, and the realities of the Late Bronze Age-Early Iron Age transition proved to be more complex and regionally diverse than a simple migration model would explain. Additionally, the gradual rejection of culture-history as a theoretical paradigm in the mid-20th century made it more difficult for archaeologists and historians to deploy migrations as straightforward and unilinear explanations for material and linguistic change, or for the development of regional ethnic identities. Nevertheless, a minimally-modified historical narrative of Dorian migration continues to have valence in scholarship even as the surge in popularity of aDNA studies has helped to revive theoretical and scientific interest in tracing ancient mobility, at least in prehistory. This article presents a regional case study exploring this phenomenon in archaeological scholarship about the Early Iron Age (EIA) on Crete (see Figure 1).